2013
DOI: 10.1063/1.4813821
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric environment effect on carrier mobility of graphene double-layer structure

Abstract: We have theoretically studied the dielectric environment effect on the charged-impurity-limited carrier mobility of graphene double-layer structure (GDLS) on the basis of the Boltzmann transport theory. In this system, two graphene layers are separated by a dielectric barrier layer. It is pointed out that the carrier mobility strongly depends on the dielectric constant of the barrier layer when the interlayer distance becomes larger than the inverse of the Fermi wave vector. Moreover, the conditions to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It is obvious that we also get the resistivity of a single graphene layer by considering a very large d value. Moreover, it has been shown that [24] the dielectric constant between the two layers in double-layer graphene systems has a significant role in transport properties. Although increasing the dielectric constant screens the interlayer interaction, it has a significant role on the intralayer screening of the considered layer too.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…It is obvious that we also get the resistivity of a single graphene layer by considering a very large d value. Moreover, it has been shown that [24] the dielectric constant between the two layers in double-layer graphene systems has a significant role in transport properties. Although increasing the dielectric constant screens the interlayer interaction, it has a significant role on the intralayer screening of the considered layer too.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…We have pointed out that the carrier mobility of GDLS strongly depends on the dielectric constant of the barrier layer when the interlayer distance becomes larger than the inverse of the Fermi wave vector 26) . However, we have considered only the case in which the carrier concentrations at each layer are equivalent (n…”
Section: Introductionmentioning
confidence: 99%
“…We have pointed out that the carrier mobility of GDLS strongly depends on the dielectric constant of the barrier layer when the interlayer distance becomes larger than the inverse of the Fermi wave vector. 26) However, we have considered only the case in which the carrier concentrations at each layer are equivalent (n ð1Þ c ¼ n ð2Þ c ), and have neglected carrier density polarization, for simplicity. Since the carrier density at each layer can be controlled by adjusting the gate voltage in the experiments, it is necessary to develop a theory that takes carrier imbalance into account.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, it is crucial to seek an alternative structure for enhancing the MFP of SC-MLGNR. Over the past few years, it is reported that the carrier mobility of GNR layers can be improved by inserting the high-k dielectric layer between two adjacent GNR layers, hence its MFP could be improved [16], [18]. This can restrict SC-MLGNR to turn into the graphite and improve the total number of graphene layers of SC-MLGNR interconnects.…”
mentioning
confidence: 99%